A domain-independent interaction integral method for evaluating the dynamic stress intensity factors of an interface crack in nonhomogeneous materials. (1st December 2016) - Huang, Kai; Guo, Licheng; Yu, Hongjun; Jia, Pengfei; Kitamura, Takayuki
Highlights: A new DII-integral for evaluating the DSIFs of an interface crack is proposed. The domain-independence of the DII-integral is proved rigorously and numerically. The present DII-integral is available for the cases with complicated interfaces. The influence of material nonhomogeneity on DSIFs is investigated. Abstract: We propose a new domain-independent interaction integral (DII-integral), which can evaluate the dynamic stress intensity factors (DSIFs) of an interface crack in nonhomogeneous materials under dynamic loading conditions. The DII-integral is rigorously proved to be domain-independent of arbitrary interfaces emerged in the integral domain. Since no material property derivative is involved in the DII-integral formulation, it can be applied to the interface crack problems with both differentiable and non-differentiable material properties. By using the extended finite element method (XFEM) combined with the DII-integral, several benchmark problems are investigated to examine the validity of the proposed DII-integral and the influence of material nonhomogeneity on the DSIFs. The results show that the present DII-integral is effective and efficient to evaluate the DSIFs of an interface crack in nonhomogeneous materials.